Quantitative Changes and Transformation of the SME Sector after the Shocks of 2022 - A. A. Blokhin; K. V. Glukhov (Мир новой экономики, 2025)
The aim of the article is to dentify structural changes in the SME sector, indicating positive dynamics and qualitative transformations of the sector during the adaptation of the Russian economy to the shocks of 2022. The methods of the research is based on a rapid analysis of a representative sample of companies in the SME sector over the past five years. It considers its industry and institutional parameters, such as the type of activity, company scale, interaction with large businesses, belonging to individuals or legal entities. The relevance of the topic is determined by the need for a holistic understanding of the role and interaction of sectors in the development of the Russian economy in the current conditions. The significant role of the SME sector is confirmed in generating income for large-size dominant companies, which thus receive institutional rent. Such a vision is necessary both for forecasting the development of sectors and for restructuring public policy from paternalistic support to the logic of transformation management.